"I have been rejected so many times" experiences of female adolescents living with HIV in rural Manzini, Eswatini: A case study. (2021) - Nsibandze, Bonisile S.; Downing, Charlene; Poggenpoel, Marie; Myburgh, Chris P.H.
Abstract: The prevalence of HIV among adolescents is increasing in Eswatini with the burden of infection being disproportionately on female adolescents. There has been limited published research on the experiences of female adolescents living with HIV. The aim of this study was to explore and describe the experiences of female adolescents living with HIV in rural Manzini region of Eswatini. The study was conducted in rural Manzini region, in the Mliba and Mafutseni areas of the country. A qualitative, exploratory, descriptive, and contextual design within a phenomenological approach was used. A purposive sample of case studies of six female adolescents living with HIV aged 18 to 21 years were recruited from clinics in the rural Manzini Region. In-depth individual phenomenological interviews were conducted with female adolescents to explore experiences of living with HIV. Interviews commenced with the central question: "How is it for you to live with HIV?" Data were transcribed verbatim and analysed thematically following Giorgi's coding method. Three themes were identified from the data: (1) experienced the quest to survive, (2) experienced support system and (3) experienced psychological effects. Female adolescents experienced hardships associated with poverty involving the lack of food and financial support for daily provision. Negative psychological effects included unresolved grief, fear of stigma and discrimination, rejection, isolation, loneliness and suicidal ideation. The disrupted social systems for female adolescents living with HIV have implications for the development of programs that provide psychosocial support to female adolescents as they navigate the adolescence stage whilst living with HIV.